Qualification Strategy and Plan for Integrated Modular Avionics for Space Separation Kernel - Butterfield, Andrew (My University, 2016)
The project IMA-SP Kernel Qualification Preparation (IMAKQP) is an ongoing activity led by SciSys Ltd, involving CNES, Airbus DS, TASF, looking at the approach to be adopted for IMA-SP Separation Kernel qualification. The activity Formal Methods Expert to IMA- SP Kernel Qualification Preparation (FMEIMAKQP) 1 is a parallel joint activity involving Lero@TCD, exploring the potential role that formal verification techniques might play in a future kernel qualification process. It follows on from the experience of a previous activity Method and Tools for Onboard Software Engineering (MTOBSE)
ESA Communications, ESTEC, NL
DASIA 2016 DAta Systems In Aerospace